2001
DOI: 10.3109/07853890109002097
|View full text |Cite
|
Sign up to set email alerts
|

Hypopituitarism and atherosclerosis

Abstract: In the last decade, retrospective cohort data has provided evidence of premature atherosclerosis in patients with hypopituitarism which may account for the recently observed increased death rate from vascular events in these patients. The exact mechanism(s) for such propensity to atherosclerotic vascular disease is not yet completely clear. It is possible that hormonal factors may be the initiating mechanisms with subsequent secondary metabolic abnormalities acting as risk factors for development of atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Pons protect LDL and HDL from oxidation, thus preventing the development of atherosclerosis and other cardiovascular diseases (Aviram and Rosenblat, 2005). Adult patients with growth hormone deficiency are predisposed to premature atherosclerosis and other cardiovascular diseases (Twickler et al, 2000;Elhadd et al, 2001). Growth hormone replacement in GH-deficient adult patients improves their LDL-cholesterol abnormalities (Twickler et al, 2000;Abdul Shakoor and Shalet, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Pons protect LDL and HDL from oxidation, thus preventing the development of atherosclerosis and other cardiovascular diseases (Aviram and Rosenblat, 2005). Adult patients with growth hormone deficiency are predisposed to premature atherosclerosis and other cardiovascular diseases (Twickler et al, 2000;Elhadd et al, 2001). Growth hormone replacement in GH-deficient adult patients improves their LDL-cholesterol abnormalities (Twickler et al, 2000;Abdul Shakoor and Shalet, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A very small number of case-control studies suggested the presence of a mild to moderate prothrombotic state in adult patients with GH deficiency, which could partly contribute to the increased risk for arterial and venous thrombosis seen in hypopituitarism (88)(89)(90)(91). Increased circulating levels of VWF, thrombomodulin, and some endothelial adhesion molecules (such as intercellular adhesion molecule-1 and E-selectin) were observed by Elhadd et al in 52 GH-deficient adults (91).…”
Section: Gh Deficiencymentioning
confidence: 99%
“…Endocrine abnormal-ities, including gonadotropin deficiencies, have also been demonstrated in recent studies to contribute to ischemic stroke (Bondanelli et al, 2006). There are a few published reports concerning hypogonadism associated with atherosclerosis in young adults (Elhadd, Abdu, & Clayton, 2001;Erfurth et al, 2002).…”
Section: Introductionmentioning
confidence: 94%